Prediction of the particle size and flow characteristics of powder blends for tableting by near-infrared spectroscopy and chemometrics - Rares Iovanov; Andreea Loredana Vonica; Ioan Tomuta (Amaltea Medical Publishing House, 2021)
The purpose of this research was to apply near-infrared (NIR) spectroscopy in combination with chemometrics to predict particle size and flow characteristics of a meloxicam powder blends for tableting. In order to develop calibration models for particle size (mean particle size, poly-dispersion index), and flow properties (angle of repose and time of flow) prediction, the NIR reflection spectra of different meloxicam powder blends prepared according to an experimental design were analyzed using different preprocessing methods by partial last-square (PLS) regression followed by leaveone-out cross-validation. Very good prediction ability was found for mean particle size, poly-dispersion index, angle of repose, and time of flow in models in whose development no preprocessing spectrum was applied. Also, a good prediction was found preprocessing spectrum such smoothing - moving average for particle size characteristics, and unit vector normalization for powder flow properties. Therefore, NIR-chemometric methods developed in this work can be useful for the prediction of the granulometric properties and parameters related to the flowability of the meloxicam powder blends and may be used as process analytical technology (PAT) tools for process control during meloxicam tablets manufacturing.